Microstructure and diffusion mechanisms in nano-Cu sintered joints during aging: Effects of joint size, porosity, and aging atmosphere - Wang, Shuaiqi; Zou, Guisheng; Huo, Jinpeng; Du, Rongbao; Liu, Lei (Microelectronics and reliability, 2025)
Sintering bonding by nano-Cu is receiving great interests in die bonding of both power electronics and integrated circuits (IC) due to its low cost compared with nano-Ag/Au. However, oxidation of sintered Cu joints, having nanoporous microstructure, remains a concern for the reliability. This study systematically studied the effects of joint size, porosity, and aging atmosphere on the oxidation mechanisms of sintered Cu. An abnormal void growth was observed for the first time in low-porosity (4.27 %) Cu bumps (60 μm diameter) during high-temperature ambient aging, which was not observed in large-area sintered Cu (3 × 3 mm2). A hypothesis was proposed based on diffusion driven by oxidization. It indicated that the microscale bump size caused high chemical potential gradient between the nanoporous Cu and the Cu2O surface oxide, leading to a massive Cu atom diffusion through grain boundaries. Vacuum aging showed Ostwald ripening in bump center and vacancies in bump edge diffusing out of bumps, which was totally different from ambient condition. For high-porosity (17.12 %) Cu bumps, oxide was directly formed inside voids due to the penetration of O2 through the connected voids. The findings revealed the oxidation mechanisms in microscale sintered Cu interconnects, which was essential for the advanced packaging of both IC and power electronics. [Display omitted] •Abnormal void growth in microscale sintered Cu bumps due to oxidation.•Microscale joint size causes high diffusion driving force between Cu and Cu2O.•Multiple oxidation mechanisms of sintered Cu with low/high porosity are unraveled.•Cu joints show better long-term performance in vacuum than ambient condition.